Pengenalan Literasi Finansial Awal Pada Anak Usia Dini Di TK Aqidah Palangka Raya - Aghnaita Aghnaita; Ali Iskandar Zulkarnain; Annisa Rahmasari; Arda Sulis Mutiara; Devi Oktavia; Ervina Ervina; Indah Koswara (Pakis Journal Institute, 2024)
This community service is motivated by the importance of introducing learning to children, especially in introducing edupreneur activities. Based on this, it is necessary to provide an introduction to edupreneur activities in terms of introduction to make children have an edupreneur spirit through activities to introduce children to early financial literacy. The aim of this community service is so that children can learn about educational activities that have been carried out, namely activities to introduce early financial literacy, and through these activities it can also teach children about transactions when selling, namely the existence of sellers and buyers using money. The target participants for this community service are children aged 5-6 years who are at the Palangka Raya Aqidah Kindergarten and students of the Early Childhood Islamic Education Study Program, Faculty of Tarbiyah and Teacher Training, IAIN Palangka Raya who are also actively involved in this activity. The results of this community service show that the children are very enthusiastic about participating in the initial financial literacy introduction activities that have been carried out at Bank Indonesia (BI) and the children look enthusiastic. The hope is that through the introduction of edupreneur activities carried out in early childhood, it will be able to stimulate children's cognitive abilities in recognizing early financial literacy, introduce children to the importance of edupreneurship for children, and increase children's experience because they have carried out edupreneur activities, namely through the introduction of early financial literacy. So that the aim of the introduction will be achieved optimally.